2010
DOI: 10.2172/974954
|View full text |Cite
|
Sign up to set email alerts
|

Technical Challenges of Plug-In Hybrid Electric Vehicles and Impacts to the US Power System: Distribution System Analysis

Abstract: Replacing a significant portion of the nation's light vehicle fleet with plug-in hybrid electric vehicles (PHEVs) offers the potential of reducing our dependence on petroleum fuels together with important economic and environmental benefits. The electric power grid is built to support peak loads and, as a consequence, suffers from low asset utilization rates in off-peak periods. In principle, this under-utilized capacity could effectively power a national fleet of PHEVs with little need to increase the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…While each of the charging units has the ability to vary their output in a continuous manner, the charging rate limits are defined in (2), where P EVmax is the rated output of each charging unit.…”
Section: Constraintsmentioning
confidence: 99%
“…While each of the charging units has the ability to vary their output in a continuous manner, the charging rate limits are defined in (2), where P EVmax is the rated output of each charging unit.…”
Section: Constraintsmentioning
confidence: 99%
“…The research reported in [1] and [9] considered the management of PHEVs in traditional distribution networks As the smart grid technologies advance, it is necessary to study PHEV's interface to future smart distribution networks. We are facing great challenges in how to utilize the smart distribution network technologies (e.g., smart meters) to provide service to more PHEVs and how to reduce cost while developing a new paradigm of distribution networks with more reliable and flexible control strategies.…”
Section: Supervisory Adaptive Control Of Smart Distribution Networkmentioning
confidence: 99%
“…term problems (i.e., undesired power quality and compromised system stability and reliability) and long term issues such as reduced lifetime of distribution transformers if they are overloaded [1], [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, as EV penetration increases, the extra demand due to EV charging will have a considerable impact on the design and operation of electrical power systems [4]. In [5][6][7][8][9][10], it has been shown that the widespread adoption of EVs could negatively impact the distribution network if charging is not properly coordinated. Grid impacts of uncoordinated charging include, but are not limited to, increased voltage imbalance [7], increased grid losses [8], overloading [6], fluctuation of grid frequencies [11], and increased harmonic distortion [12].…”
Section: Introductionmentioning
confidence: 99%